Evidence Based Study of Surasadi Gana on Respiratory Disorders: A Review (International Journal of Ayurveda and Pharma Research, 2023)
Introduction: Collection of medicinal herbs having similar effect are collectively known as Gana (group) in Samhita and Vargas (category) in Nighantu. Surasadi Gana is included in 37 of such groups mentioned in Sushruta Samhita, with 21 Herbs completing the group. This article is made in a view to review the importance and utility of few herbs included in Surasadi Gana indicated for the management of respiratory disorders.Material and Methods: The literature regarding the drugs mentioned in the group, collected from different Ayurveda classics. Research papers are compiled from published sources and discussed in light of therapeutic effects.Observation and Result: Maximum of the herbs in this group are having properties as Katu rasa (pungent) and Ushna veerya (hot potency). Such herbs are predominantly advised in Kapha (phlegm humour) dominant diseases, viz. Kasa (cough), Shwasa (asthma), Pratishyaya (common cold), Kushtha (skin disorders), Krimi (worm infestation) and Vrana (wound).Conclusion: The herbs, despite having several Ayurvedic indications, the respiratory tract is the focus of the specific activity.